2013
DOI: 10.1063/1.4819144
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the effects of superhydrophobic surface on skin-friction drag in turbulent channel flow

Abstract: Superhydrophobic surfaces have attracted much attention lately as they present the possibility of achieving a substantial skin-friction drag reduction in turbulent flows. In this paper, the effects of a superhydrophobic surface, consisting of microgrates aligned in the flow direction, on skin-friction drag in turbulent flows were investigated through direct numerical simulation of turbulent channel flows. The superhydrophobic surface was modeled through a shear-free boundary condition on the air-water interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
160
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(192 citation statements)
references
References 38 publications
31
160
1
Order By: Relevance
“…The recent numerical (Martell et al 2009(Martell et al , 2010Park et al 2013) and experimental (Daniello et al 2009) results under turbulent flow conditions have shown that SHPo surfaces with even a moderate slip length (~10 µm) can result in significant turbulent drag reduction, as the turbulent structures become weakened near the SHPo surface and a thin viscous sublayer becomes the main characteristic fluidic length scale in the turbulent flow. Recently, using regular-structured SHPo surfaces of large slip lengths, drag reductions as much as 75 % have been reported in turbulent boundary layer flows (Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The recent numerical (Martell et al 2009(Martell et al , 2010Park et al 2013) and experimental (Daniello et al 2009) results under turbulent flow conditions have shown that SHPo surfaces with even a moderate slip length (~10 µm) can result in significant turbulent drag reduction, as the turbulent structures become weakened near the SHPo surface and a thin viscous sublayer becomes the main characteristic fluidic length scale in the turbulent flow. Recently, using regular-structured SHPo surfaces of large slip lengths, drag reductions as much as 75 % have been reported in turbulent boundary layer flows (Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum DR achievable in turbulent channel flows has been explained by the effective slip length in wall unit (λ + = λu τ /ν) through numerical simulations (Fukagata et al 2006;Busse & Sandham 2012;Park et al 2013). They showed that to obtain a substantial DR, the slip length should be comparable to the viscous sublayer thickness, i.e., λ + ~ 5, and that the DR would saturate if the slip length reaches a very large value, λ + = O(10 2 ).…”
Section: Scalingmentioning
confidence: 99%
“…However, such a relationship has yet to be established for turbulent flows (Park et al 2013). While the analytical, numerical and experimental results of SHPo drag reduction converged finally for laminar flows (Lauga & Stone 2003;Ou et al 2004;Maynes et al 2007;Woolford et al 2009a), the studies of turbulent flows have mostly been numerical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That famous talk is often credited with kick-starting nanotechnology. Many current construction problems and requirements of construction processes can be enhanced using nanotechnology, generating products with many unique characteristics: lighter and stronger structural composites; low-maintenance coatings; better cementitious materials; lower thermal transfer rate of fire retardant and insulation; better sound absorption of acoustic absorbers and better reflectivity of glass (Zhu et al, 2004); superhydrophobic surfaces, which have attracted much attention lately as they present the possibility of achieving a substantial skin-friction drag reduction in turbulent flow (Park et al, 2013). This is a typical example of a multidisciplinary approach, the core of our journal, which will become much more fundamental in the future.…”
mentioning
confidence: 99%